Diversity of spiders in Fanjing Mountain Nature Reserve, Guizhou, China, I: Six new species of Phrurolithidae (Araneae) - Wang, Lu-Yu; Chen, Hui-Ming; Zhou, Ke-Xin; Zhang, Feng; Zhang, Zhi-Sheng (Zootaxa, 2015)
Male and female specimens of six new spider species of the family Phrurolithidae were collected from the Fanjing Mountain Nature Reserve: Otacilia microstoma sp. nov., O. songi sp. nov., O. subliupan sp. nov., Phrurolithus anticus sp. nov., P. fanjingshan sp. nov. and P. zhouyun sp. nov.. Photographs, line drawings and descriptions of all species are provided in the current study. Additionally, the assignment of each species has been discussed on the basis of the type species of Otacilia Thorell, 1897 and Phrurolithus C. L. Koch, 1839.